Técnicas de geoprocessamento na determinação do índice de perigo de incêndios - Illana, Vinícius Borges (2006)
The forest fire is considered an environmental impact, because provokes physic, biotic and anthropic environment characteristics changes or modifications. Brasil doesn't have an adequate fire politic support. It's necessary to obtain more precise information about the national territory, like the area size, existence of accesses ways and artificial lakes, land relief, climatic and vegetation characteristics. These informations are essential to define the most significant fire risk regions and establish intensive fire prevention programs. The actual research objectivates the knowledge and techniques aplications about SR, SIG, geoprocessing and forest fires to elaborate the Combustion and Fire Ignition Dangerous Levei to the hydrographic micro basin of the Ibicuí Mirim river sources. The study area is located in the central part of the Rio Grande do Sul State between the coordinates 29°26'32" to 29°33'57 of south latitude and 53°40'49" to 53°48'27 of west latitude. Are 8454,10 hectares of total area, from which approximately comes 60% of the water that is consumed in the city of Santa Maria. The city digital cartographic base used was elaboreted from existent analogic datas (topographic maps - 1:50.000 scale), besides the digital mosaico It was executed elaboration plans throught Pls crossing, providing informations used in the Fire Dangerous Levei elaboration. With the geoprocessing knowledge and techniques aplications, SR, SIG and forest fire, became possible to develop the Fire Dangerous Levei to the studied areas. Thus, with the results, preventive actions can be implemented like: fire towers, construction of artificial lakes, cleaning and the improvement of the actions in the forest to the environment protection.